A Conceptual Analysis of Linguistic, Organizational, and Affective Challenges in EFL Descriptive Writing - Sarah Theodora Wahyuni Lumbantobing; Selviana Napitupulu (CV. Doki Course and Training, 2026)
This study aims to conceptually examine the linguistic, organizational, and affective challenges encountered by EFL learners in writing descriptive texts. Employing a qualitative conceptual approach, the study critically synthesizes findings from relevant empirical and theoretical studies on EFL writing, with particular attention to the Indonesian context. The analysis reveals that students’ writing difficulties are not solely rooted in linguistic limitations such as grammar and vocabulary, but are also closely associated with weaknesses in text organization and affective factors, including writing anxiety, low self-confidence, and fear of making errors. Importantly, these challenges are found to be interrelated, whereby linguistic difficulties tend to intensify affective barriers, which subsequently hinder learners’ ability to organize ideas coherently. The theoretical contribution of this study lies in its integrative conceptual framework that positions linguistic, organizational, and affective dimensions as mutually reinforcing components of EFL writing difficulties, extending previous research that has predominantly examined these aspects in isolation. The study concludes that pedagogical responses to EFL writing challenges should adopt a holistic approach that simultaneously addresses language form, text structure, and learners’ emotional engagement in the writing process.